Theories of Programming and Formal Methods Essays Dedicated to Jifeng He on the Occasion of His 80th Birthday - Bowen, Jonathan P.; Li, Qin.; Xu, Qiwen (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This Festschrift volume, dedicated to Jifeng He on the occasion of his 80th birthday, includes refereed papers by leading researchers, many of them current and former colleagues, presented at a dedicated celebration in the Shanghai Science Hall in September 2023. Jifeng was an important researcher on the European ESPRIT ProCoS project and the Working Group on Provably Correct Systems, subsequently he collaborated with Tony Hoare on Unifying Theories of Programming. Jifeng returned to China in 1998, first to the United Nations University in Macau and then to the East China Normal University in Shanghai. He has since founded an Artificial Intelligence research institute that focuses on the application of technology in large-scale industrial software systems. His scientific contributions have been recognized through his election to membership of the Chinese Academy of Sciences. The first paper in the volume provides an overview of Jifeng's research contributions, especially in the area of formal methods, and the following two papers detail developments in UTP and rCOS (refinement calculus of object systems). In the next two sections of the book, the editors included papers by colleagues and coauthors of Jifeng while he was at the University of Oxford and engaged with the European ProCoS project. The section that follows includes papers authored by colleagues from his later research in China and Europe. The final section includes a paper related to Jifeng's recent roadmap for UTP.
Jifeng He's Research Influence -- Oxford Colleagues -- ProCoS Colleagues -- Chinese Colleagues -- European Colleagues -- The Future Roadmap.
Keywords: Software engineering; Computer science; Software Engineering; Computer Science Logic and Foundations of Programming